Surgical management of a large radicular cyst using modified guided tissue regeneration techniques: a case report with 4 years follow‐up. (27th May 2019) - Camargo, J.M.P.; Braga, T.; Camargo, R.; Love, R.M.; Reher, P.
Abstract: This case report discusses the management of a large radicular cyst using current periapical surgery techniques associated with the use of modified guided tissue regeneration (GTR) techniques. The cyst involved several anterior teeth and measured 40 mm in its widest dimension, involving both cortical plates, and extending into the floor of the nose. The surgical endodontics techniques used here included the use of enhanced magnification, minimal root resection, ultrasonic root‐end preparation and retrograde obturation with a bioceramic root repair material. The large bone defect was reconstructed with the use of a mixture of autogenous bone harvested from the mandibular ramus, Bio‐oss® and platelet‐rich fibrin (PRF), covered with a thin PRF membrane acting as a modified GTR. The combination of these techniques ensured successful clinical, radiographic and tomographic outcomes after 4 years of follow‐up.